Reviewing the Status of Turtles in Kenyan Aquatic Ecosystems: Threats and Current Conservation Efforts - Ogello, Erick; Kinga, Jeniffer; Mwanzia, Janet; Outa, Nicholas; MUTHOKA, MAVINDU (My University, 2022)
Turtles are ancient repltiles with significant economic, ecological and social values to humanity. Due to the high demand for commercialized sea turtle products, turtles have been classified under ‘Critically Endangered’, ‘Endangered’ or ‘Vulnerable’ by the World Conservation Union. The long-term survival of turtles is contingent on the protection of nesting areas and the education of local communities on their conservation and importance. Pollution, loss of nesting grounds, bycatch in fishing, poaching, and climate change contribute to the decrease of turtles. If these causes are left unchecked, they may have devastating effects on the turtle population. Long-term monitoring is therefore essential for gaining a thorough understanding of turtle population dynamics and assessing the efficiency of conservation measures. We conducted a review of the most recent literature to guide future research, emphasizing the basic biology of turtles with a focus on the Kenyan situation. The review has revelaed that Kenya is home to a variety of turtles, including both marine and freshwater turtles. The green turtle (Chelonia mydas), hawksbill turtle (Eretmochelys imbricata), loggerhead turtle (Caretta caretta), Olive Ridley turtle (Lepidochelys olivacea), and leatherback turtle (Dermochelys coriacea) are some of the marine turtles found in Kenyan waters. The paper further discusses the importance of turtles, the risks they face, presents conservation measures as well as what can be done to raise their survival rates. This review proposes that government, non-governmental organizations and community must devote special attention to the development and execution of scientifically sound, conservation measures to reduce activities that place turtles under threat.
This is a Review of the Status of turtles in Kenya, the threats they face and the current conservation efforts and the suggestions on the best ways forward.
Keywords: Turtles; Conservation; Endangered